All Days 2002
DOI: 10.2118/75715-ms
|View full text |Cite
|
Sign up to set email alerts
|

General Correlation for the Effect of Non-Darcy Flow on Productivity of Fractured Wells

Abstract: The paper describes a systematic study of the effect of the turbulence on productivity (or injectivity) of fractured wells. It extends significantly beyond previous work, and shows its limitations. A new correlation has been developed, based on over 2,000 high-accuracy numerical solutions for vertically fractured well for a simple geometry. The base correlation was developed for fully penetrating fracture and it is applicable to liquid and high-pressure gas systems. The general correlation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…A partial answer comes from Settari and Bale. 4 An extensive finite difference model study found that "…. All simulation data was below the straight line of Eq.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…A partial answer comes from Settari and Bale. 4 An extensive finite difference model study found that "…. All simulation data was below the straight line of Eq.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…Settari et al (2000) demonstrated that examining the effect of turbulence is critical, as negative skin from fracturing can cancel-out the effect of positive skin due to turbulence. In a further work, Settari et al (2002) noted that turbulence effect on productivity or injectivity can be significant for liquid flow in high permeability formations (which also implies wells with high conductivity such as high rate wells) having limited perforations. Ajab and Yu-Shu (2011) in their research on modeling non-Darcy flow for pressure transient analysis on porous and fractured reservoirs (which are synonymous to reservoirs produced by high rate wells) illustrated that an increase in the production rate can result in significant increase in pressure drop at the wellbore resulting from non-Darcy flow effects especially for high production rates.…”
Section: Non-darcy Flow Effects (Rate-dependent Skin) In Petroleum Rementioning
confidence: 99%
“…Recent publications 30,42 have proven that MHF treatments are not only used in low-permeability gas reservoirs to enhance the productivity, but they are also applied to highpermeability reservoirs. The ultimate goal of the treatment in this case is to reduce the non-Darcy flow effects around the wellbore.…”
Section: Effect Of Reservoir Permeabilitymentioning
confidence: 99%